A place inside of me : a poem to heal the heart - Elliott, Zetta (Farrar Straus Giroux Books for Young Readers, 2020)
Illustrations and easy-to-read text express a child's awareness of being filled with deep emotions, from joy to sorrow and anger to compassion, but above all, love.